Management of foot rot and bakanae of rice through fungicides - ANIL KUMAR, PANKAJ KUMAR, S. SUNDER, RAM SINGH* and (Indian Phytopathology, 2016)
Foot rot and bakanae caused by Fusarium fujikuroi Nirenberg [teleomorph: Gibberella fujikuroi (Sawada) Wollenweber] is a major production constraint in export quality Basmati rice in Haryana. In vitro growth inhibition tests of six fungicides revealed that the EC50 values of fungicides varied from 0.34 to 724.43 ppm a.i. Trifloxystrobin 25% + tebuconazole 50% 75 WG was the most inhibitory (EC50 0.34 ppm a.i.). In terms of EC90 values, carbendazim 50 WP was the most toxic (EC90 1.14 ppm a.i.) followed by tebuconazole 250 EC and trifloxystrobin 25% + tebuconazole 50% 75 WG with EC90 values of 3.89 and 4.36 ppm. Field trials conducted in nursery beds and transplanted crop indicated that all the fungicides and a biocontrol agent Trichoderma viride reduced bakanae incidence significantly. Tebuconazole 250 EC, trifloxystrobin 25% + tebuconazole 50% 75 WG and kresoxim methyl 44.3 SC (statistically on par) were found to be highly effective in reducing the disease incidence in both the cultivars closely followed by carbendazim 50 WP and azoxystrobin 44.3 SC. In transplanted crop also, tebuconazole 250 EC was observed to be the most effective in reducing bakanae incidence and enhancing grain yield of paddy. Seed treatment with T. viride at 5 g/kg seed provided about 60 per cent disease control in both the cultivars. A significant increase in grain yield was also observed in each treatment.